TINJAUAN YURIDIS TERHADAP STRUKTUR NOMINEE PEMEGANG SAHAM (NOMINEE STRUCTURE) DALAM SUATU PERSEROAN TERBATAS - HENDRIK TANJAYA (PREMISE LAW JURNAL, 2016)
Nominee structure is a structure resulting in a beneficiary has the power to controls the nominee, where a nominee is only as a registered owner of an object, and the beneficiary as the real owner is the one who controls, manages and earns benefits from that object. Nominee structure is often applied in the ownership of shares in a limited liability company in Indonesia. The data for this normative juridical study were obtained through documentation study in which the data obtained were systematically arranged and analyzed through a qualitative scientific logic procedure. The form of nominee shareholder structure in Indonesia is divided into direct nominee structure and indirect nominee structure. Basically the validity of a nominee shareholder structure is depends on the validity of the underlying agreement. A public notary as the competent authority who creates an authentic deed as the underlying of a nominee structure is responsible to make sure that the deed he made must comply to and does not breach the prevailing laws and regulations. It is suggested that a clear and strict regulations about the nominee shareholders should be governed in the Company Law in order to create legal certainty. Nominee shareholder structure should be allowed with special supervision and certain restrictions, considering the using of a nominee is basically indispensable in order to transact effectively and efficiently, particularly in capital markets. Keywords: Nominee Structure, Shareholders, Limited Liability Company.